2017
DOI: 10.1159/000479105
|View full text |Cite
|
Sign up to set email alerts
|

Call for Caution: Neonatal Portal Vein Thrombosis following Enbucrilate Embolization of Placental Chorioangioma

Abstract: We illustrate a case of giant placental chorioangioma presenting at 20 weeks of gestation. Subsequent monitoring revealed enlargement of the lesion, associated with fetal anemia and cardiac failure, prompting in utero intervention. Amnioreduction followed by percutaneous embolization of the tumour with enbucrilate:Lipiodol Ultra-Fluid™ at a dilution of 1:5 was successfully performed. No repeat intervention or additional supportive measures were required throughout pregnancy and the baby was delivered at 36 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The search identified 322 articles, of which 68 were assessed in full text with respect to their eligibility for inclusion (Table S1) and 28 studies were included in the systematic review (Table S2, Figure 2) [1][2][3][4]6,7,9,10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . These 28 studies included 161 singleton pregnancies (144 from cohort studies and 17 from case reports) affected by placental chorioangioma without associated structural anomalies.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search identified 322 articles, of which 68 were assessed in full text with respect to their eligibility for inclusion (Table S1) and 28 studies were included in the systematic review (Table S2, Figure 2) [1][2][3][4]6,7,9,10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] . These 28 studies included 161 singleton pregnancies (144 from cohort studies and 17 from case reports) affected by placental chorioangioma without associated structural anomalies.…”
Section: General Characteristicsmentioning
confidence: 99%
“…These 28 studies included 161 singleton pregnancies (144 from cohort studies and 17 from case reports) affected by placental chorioangioma without associated structural anomalies. Of these studies, 11 were cohort studies [1][2][3][4]6,7,[19][20][21][22][23] , while 17 were case reports of pregnancies undergoing in-utero treatment of the chorioangioma (Table S2) 9,10,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] .…”
Section: General Characteristicsmentioning
confidence: 99%
“… 7 Embolization has been performed with liquid agents such as ethanol, cyanoacrylate, and enbucrilate. 8 9 10 Chorangiomas, however, may contain arteriovenous anastomoses, which can allow for passage of liquid or small particulate embolic agents through the tumor and back to the fetus. Voon et al recently reported a case of portal vein thrombosis in a newborn after use of the liquid embolic agent enbucrilate and advised caution with this material.…”
Section: Discussionmentioning
confidence: 99%
“…Chorioangiomas are typically small masses without clinical consequences, however, large chorioangiomas, typically lesions larger than 4 cm, can cause hydramnios, arteriovenous (AV) shunting, and fetal red blood cell (RBC) sequestration. AV shunting and RBC sequestration can lead to fetal anemia, non-immune hydrops fetalis, fetal cardiomyopathy, intrauterine fetal growth restriction (IUGR), and even fetal demise [19][20][21][22]. Chorioangiomas are diagnosed via ultrasonography as well circumscribed solid or complex masses located on the fetal side of the placenta with turbulent hypervascular flow on Doppler-flow imaging.…”
Section: Part 1: Intrinsic Placental Abnormalitiesmentioning
confidence: 99%
“…Chorioangiomas are diagnosed via ultrasonography as well circumscribed solid or complex masses located on the fetal side of the placenta with turbulent hypervascular flow on Doppler-flow imaging. Management depends on the size of the mass, evidence of hydramnios, and evidence of fetal compromise, with management ranging from amnioreduction, percutaneous intrauterine transfusion, and embolization or laser coagulation of feeding vessels [20][21][22].…”
Section: Part 1: Intrinsic Placental Abnormalitiesmentioning
confidence: 99%